Radiation and viscous dissipation affect MHD casson hybrid nanofluid flow over a sheet through a porous medium - Rehman, Ali; Saad, Abdullah Aziz Bin; İnç, Mustafa; Salleh, Zabidin; Alsubaie, Abdullah Saad; Sudarmozhi, K. (Elsevier, 2025)
This current research investigates the combined possessions of viscous dissipation and radiation on magnetohydrodynamic (MHD) Casson hybrid nanofluid (HNF) flow via a stretching sheet embedded in a permeable medium. The HNF consists of 2 different nanoparticles, alumina Al2O3 and molybdenum disulphide MoS2 deferred in a base fluid of blood, aiming to increase the thermal conductivity beyond that of conventional nanofluids. A two-dimensional, steady, incompressible boundary-layer flow is considered, incorporating the nonNewtonian properties of a Casson fluid. The governing PDEs accounting for velocity and energy are transformed into a system of nonlinear ODEs through similarity transformations. These transform equations are seminumerically answered via the BVPh 1.0 and BVPh 2.0 in Mathematica with HAM. These Parametric studies show that increasing the radiation parameter and Eckert number significantly enhances the temperature distribution, while the occurrence of a magnetic field and porous medium resistance suppresses the velocity field. Also, the HNF establishes superior heat transfer performance compared to single nanoparticle suspensions. The results provide valuable insights into optimizing industrial and biomedical processes involving non-Newtonian HNFs under thermal and magnetic conditions.
Keywords: Thermal radiation; Heat transfer; Stretching surface